Combined nanoindentation and SEM imaging for phase quantification and creep prediction of cementitious materials - Imane Bekrine; Benoit Hilloulin; Ahmed Loukili (Materials & Design)
The present article introduces a novel and rapid method for processing nanoindentation data using SEM image analysis, called Auto-NI-SEM (Automatic NanoIndentation-Scanning Electron Microscopy). The originality of the method lies in the exploitation of micromechanical data, coupled with image analysis, by developing a suitable automatic deconvolution method. The method leads to a rapid phase quantification of cement paste phases along with their elastic and viscoelastic properties, essential for accurate prediction of macroscopic properties. The results were validated on cement pastes with different water-to-cement (w/c) ratios. Furthermore, the method was found to be reliable for the detection of minor phases, such as for portlandite in low water-to-cement ratios cement pastes, whose volume fractions are in line with those measured by thermogravimetric analysis. Finally, the refined properties helped to accurately predict the cement pastes creep using an analytical homogenization scheme, which was confirmed by microindentation measurements.